Design of a Module for Cultivation of Tuberous Plants in Microgravity: The ESA Project “Precursor of Food Production Unit” (PFPU) - Paradiso, Roberta; Ceriello, Antonio; Pannico, Antonio; Sorrentino, Salvatore; Palladino, Mario; Giordano, Maria; Fortezza, Raimondo; De Pascale, Stefania (Frontiers in Plant Science, 2020)
Plant cultivation systems for Bioregenerative Life-Support Systems in Space developed on Earth need to be tested in space, where reduced gravity alters the liquid and gas behavior both within the plant and between the plant and its surrounding environment, making the distribution of water and nutrients a critical issue. The ESA project “Precursor of Food Production Unit” (PFPU) aims to design a modular cultivation system for edible tuberous plants (such as potato and sweet potato) in microgravity, to be preliminary tested in ground conditions in the view of successive space application. Among the different modules of the PFPU demonstrator, the Root Module (RM) is the component physically hosting the plant and accommodating tubers and roots. This paper describes the step-by-step procedure adopted to realize the RM, including the design, the building, and the ground testing of its prototype. Specifically, the hydrological characterization of possible cultivation substrates, the set-up of the water distribution system, and the validation test of the assembled prototype in a tuber-to-tuber growing cycle of potato plants are described. Among six substrates tested, including three organic materials and three synthetic materials, cellulosic sponge was selected as the best one, based on the hydrological behavior in terms of air and water transport and water retention capacity. The water sensor WaterScout was successfully calibrated to monitor the water status in cellulosic sponge and to drive irrigation and fertigation management. The designed porous tubes-based distribution system, integrated with water sensors, was able to provide water or nutrient solution in a timely and uniform way in cellulosic sponge.